Realised added value in dynamical downscaling of Australian climate change - Di Virgilio, Giovanni; Evans, Jason P.; Di Luca, Alejandro; Grose, Michael R.; Round, Vanessa; Thatcher, Marcus (Climate Dynamics, 2020)

Projected changes in vertical temperature profiles for Australasia - Ji, Fei; Evans, Jason P.; Di Virgilio, Giovanni; Nishant, Nidhi; Di Luca, Alejandro; Herold, Nicholas; Downes, Stephanie M.; Tam, Eugene; Beyer, Kathleen (Climate Dynamics, 2020)

Rapid Warming in the Australian Alps from Observation and NARCliM Simulations - Ji, Fei; Nishant, Nidhi; Evans, Jason P.; Di Luca, Alejandro; Di Virgilio, Giovanni; Cheung, Kevin K. W.; Tam, Eugene; Beyer, Kathleen; Riley, Matthew L. (Atmosphere, 2022)
The Australian Alps are the highest mountain range in Australia, which are important for biodiversity, energy generation and winter tourism. Significant increases in temperature in the past decades has had a huge impact on biodiversity and ecosystem in this region. In this study, observed temperature is used to assess how temperature changed over the Australian Alps and surrounding areas. We also use outputs from two generations of NARCliM (NSW and Australian Regional Climate Modelling) to investigate spatial and temporal variation of future changes in temperature and its extremes. The results show temperature increases faster for the Australian Alps than the surrounding areas, with clear spatial and temporal variation. The changes in temperature and its extremes are found to be strongly correlated with changes in albedo, which suggests faster warming in cool season might be dominated by decrease in albedo resulting from future changes in natural snowfall and snowpack. The warming induced reduction in future snow cover in the Australian Alps will have a significant impact on this region.

Evaluating reanalysis-driven CORDEX regional climate models over Australia: model performance and errors - Di Virgilio, Giovanni; Evans, Jason P.; Di Luca, Alejandro; Olson, Roman; Argüeso, Daniel; Kala, Jatin; Andrys, Julia; Hoffmann, Peter; Katzfey, Jack J.; Rockel, Burkhardt (Climate Dynamics, 2019)